Strategi Promosi Perpustakaan Bangkit dalam Menumbuhkan Budaya Literasi Masyarakat Kecamatan Kota Baru Kota Jambi - Apriliani, Dewinta; Yusufhin, Fridinanti; syamsuddin, Syamsuddin (Baitul 'Ulum: Jurnal Ilmu Perpustakaan dan Informasi, 2025)
This study aims to analyze the promotion strategy of the Bangkit Library in fostering a culture of literacy in the community of Kota Baru District, Jambi City, and identify the obstacles faced. The low interest in literacy in some Jambi communities shows the urgency of a study on the effectiveness of library promotion. A descriptive qualitative approach was used to collect data through interviews, observations, and documentation. Key informants included library managers and community representatives. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The promotion strategy of the Bangkit Library includes oral promotion, distribution of pamphlets, and use of social media (Instagram, Facebook, WhatsApp, YouTube). Cooperation with the Archives and Library Service of Jambi City, Posyandu, and schools has also been established. Internal obstacles include limited funds, duplicate human resources, and limited collections. The main external factor is the lack of public interest. The findings show that although promotional efforts have been made, this obstacle hinders the optimization of increasing literacy. The Bangkit Library has implemented various promotional strategies, but is constrained by internal issues (funds, human resources, collections) and external issues (public interest). It is recommended to develop a "Thematic Mobile Library" program with interactive activities and recruit "Community Digital Literacy Ambassadors" from local residents. This innovation is expected to overcome obstacles and make promotions more effective and attractive to the community. Keywords: Promotion Strategy, Information Literacy, Public.